(untitled) (The Research of Medical Science Review, 2025)
Pakistan has an aging population, with an associated increase in the prevalence of chronic diseases. Postmenopausal osteoporosis is of particular concern because it leads to an increased risk of fractures, with subsequent negative impacts on health in older women. A descriptive cross-sectional study was designed to determine the prevalence of osteoporosis with BMD among post-menopausal women of twin cities. A total of 200 post-menopausal women of different age groups (40-70) were scanned using BMD data from DEXA scan. Out of 200 participants, 112 had Osteoporosis. The mean age of the participants was 55.09 years with S.D 6.688. Osteoporosis was present in 112 (56%) and osteopenia in 46 (23%) of the participants and only 42(21%) females had normal BMD. Study revealed that as age increases post-menopausal females had greater prevalence of osteoporosis due to low bone mineral density. Among all participants, samples of age group 60-70 years had higher prevalence of osteoporosis than any other age groups.